Operational Perspectives on Extended Producer Responsibility. (4th October 2018) - Atasu, Atalay
Summary: We revisit three important assumptions about extended producer responsibility (EPR) that originate from academia, policy, or practice: (1) A central objective of EPR should be to induce product designs for the environment; (2) collective EPR implementations mute incentives to design for the environment; and (3) more stringent EPR policy parameters will generate better environmental outcomes. We discuss the potential shortcomings of these assumptions from an operations perspective and their implications for academic and policy research.